Enhancing Water and Food Security Through Improved Agricultural Water Productivity New Knowledge, Innovations and Applications - Mabhaudhi, Tafadzwanashe; Chimonyo, Vimbayi G. P.; Senzanje, Aidan; Chivenge, Pauline P.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2025)
This open-access edited book provides a synthesis of knowledge on Water Productivity (WP) and its role in addressing global challenges related to water and food insecurity, as well as climate change. It explores how increasing WP can contribute to achieving several Sustainable Development Goals (SDGs) in the global South, with a focus on SDG 2, 6, and 12. The volume connects WP with emerging approaches such as the water-energy-food nexus, sustainable food systems, and the circular economy. It features case studies, critical analyses, and meta-analyses that bridge the science-policy-practice interface. The book also delves into WP's relation to global priorities, policies, and the empowerment of vulnerable communities, highlighting the non-negotiable rights to water and food. Governance, policies, and institutions are discussed in the context of enhancing WP in farmer-led irrigation and scaling WP technologies. The book also covers emerging methods for determining WP, assessing linkages to nutrition, health, and well-being, and integrating climate change adaptation and mitigation strategies. This is a guide for regional and international experts, professionals, and scholars interested in agricultural water management in the global south. The book has the potential to inform multi-regional and sectoral policies, particularly in Africa, and contribute to sustainable development through better resource management.
Chapter 1. A Review of existing knowledge on water use and nutritional water productivity in South Africa -- Chapter 2. Why agricultural water productivity matters: A review -- Chapter 3. Management and Agricultural Water Productivity Improvement in India and The Ganges Basin -- Chapter 4. Remote Sensing maize water stress in smallholder farms: A systematic review of progress, challenges, and the way forward using earth observation data -- Chapter 5. Application of endophytes in bioremediation, biotransformation, and water disinfection for irrigation systems -- Chapter 6. Estimating crop water productivity using remote sensing data at plot scale in an irrigation system: the case of Chisumbanje and Ratelshoek Estate -- Chapter 7. Sustainable Intensification of Mixed Farming System in West Africa: Concepts, Practices and Challenges -- Chapter 8. The Crop-Livestock-Soil Nutrient-Water Nexus in Mixed Farming System: A Research Gap in West Africa Region -- Chapter 9. Using AquaCrop, DSSAT and the SIMPLE to estimate water use of underutilised cereal in South Africa -- Chapter 10. Water Productivity in South Asia: Spatial and Temporal Variations -- Chapter 11. Nanotechnological Applications to Improving Agricultural Water Productivity -- Chapter 12. Scaling Resource Recovery and Reuse (RRR) innovations in low-and middle-income countries for climate change adaptation and mitigation -- Chapter 13. A systematic scoping review of irrigation development and agricultural water management in South Africa -- Chapter 14. A systematic review of irrigation development and agricultural water management in Mali -- Chapter 15. Opportunities to improve water productivity in farmer-led irrigation: A case study of Ethiopia -- Chapter 16. Irrigation Development and agricultural water management in Rwanda: A systematic review -- Chapter 17. Summary Crop water productivity: a catalyst for food and water security.
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, described non-text content (images, graphs), bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Agriculture; Plant physiology; Plant ecology; Agriculture; Plant Physiology; Plant Ecology